The Role of Early Warning System Components in Financial Distress: Evidence from Indonesian Islamic Banks - Rizqiyah Salsabila; Ahmad Tibrizi Soni Wicaksono; Nariman Shamakov (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2022)
This study aims to utilize the Early Warning System (EWS) component to predict the condition of Islamic banks before bankruptcy. This study uses the springate score model to measure the Financial Distress (FD) condition of Islamic banks. Samples were taken from 13 Islamic Commercial Banks for the period 2016 - 2020. The EWS components are Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Financing Deposit to Ratio (FDR) and Allowance for Impairment Losses (CKPN). Based on the springate score calculation, the highest FD conditions occurred in 2019 and 2020 due to the COVID-19 pandemic. The logistic regression test results show that only the NPF ratio has a positive effect on FD. While the CAR, FDR and CKPN variables have no effect on FD. This proves that the CAR, FDR and CKPN ratios owned by Islamic banks are said to be good so as to keep away from FD conditions.